La epistemología contable y su aporte científico en el estudio de la contabilidad. - Malla Aguilar, Jessica Sofia (Machala : Universidad Técnica de Machala, 2022)
This research work is focused on a theoretical review of accounting epistemology and its contribution to the study of accounting, related to accounting scientific research aimed at the reflective analysis of some of the epistemological currents that are an indispensable part of the scientific construct of creation and analysis of new knowledge. Making known the axiological, ontological, epistemological foundations, accounting positivism; which structure accounting knowledge, and the exploratory-technological foundation of accounting, which results in a representation of economic and social efficiency; thus developing a greater attachment to delve into the ocean of science, critically, analytically and interpretatively of accounting thought. Therefore, the epistemological nature concludes in the veracity of accounting as a social science, accompanied by other sciences that are of great importance for professional training in which a scientific connection is born in which the accounting professional applies his knowledge by strengthening theories and investigations of high epistemological contrast, thus promoting their investigative spirit that generates a contribution to society to effectively analyze the problems that arise in the business world. In this research line, emphasize control and social responsibility, which demands an ethical action of professionals in the free exercise of accounting, regarding management decision-making in the financial field with order and relevance, to maintain afloat the financial prosperity of companies and society.
Este trabajo de investigación está enfocado en una revisión teórica de la epistemología contable y su aporte al estudio de la contabilidad, relacionada con la investigación científica contable dirigido al análisis reflexivo de algunas de las corrientes epistemológicas que son parte indispensable del constructo científico de la creación y análisis de nuevos conocimientos. Dando a conocer los fundamentos axiológicos, ontológicos, gnoseológicos, positivismo contable; los cuales estructuran el saber contable, y la cimentación exploratoria-tecnológica de la contabilidad, que da por resultado una representación de eficacia económica y social; desarrollando así un mayor apego a hondar en el océano de la ciencia, de manera crítica, analítica e interpretativa del pensamiento contable. Por ende la naturaleza epistemológica concluye en la veracidad de la contabilidad como una ciencia social, acompañada de otras ciencias que son de gran importancia para la formación profesional en la cual nace una conexión científica en la que el profesional contable aplique sus conocimientos mediante el fortalecimiento de las teorías e indagaciones de alto contraste gnoseológico, promoviendo así su espíritu investigador que genere un aporte a la sociedad para analizar con eficacia los problemas que se presentan en el mundo empresarial. En tal línea investigativa hacer énfasis en el control y la responsabilidad social, que demanda una acción ética de los profesionales en el libre ejercicio de la contaduría, respecto a la toma de decisiones de la gerencia en el ámbito financiero con orden y pertinencia, para mantener a flote la prosperidad financiera de las empresas y la sociedad.
Keywords: CONTABILIDAD; EPISTEMOLOGÍA; INVESTIGACIÓN; SOCIEDAD